How the financial crisis affects pensions and insurance and why the impacts matter - Impavido, Gregorio (IMF [Washington]US, 2009)
Discusses the key sources of vulnerability for pension plans and insurance companies in light of the global financial crisis of 2008. Discusses also how these institutional investors transit shocks to the rest of the financial sector and economy.